Almotriptan: a review of 10 years' clinical experience. (October 2010) - Pascual, Julio; Vila, Carlos; McGown, Caroline C
Almotriptan, a serotonin 5-HT1B/1D agonist, was developed for the acute treatment of migraine with or without aura and has been available for 10 years. This article evaluates the wealth of experience that has been obtained with almotriptan, including large randomized clinical trials (RCTs) and post-marketing studies that more closely reflect everyday clinical practice. Initial RCTs required patients to take almotriptan when migraine pain was of moderate or severe intensity, and found that 12.5 mg provided optimal outcomes for both pain relief and tolerability. Almotriptan effectively improved 2-h pain-relief, reduced migraine-associated symptoms and demonstrated low recurrence rates. These findings were also shown in patient subgroups, such as adolescents and menstrual migraineurs. A secondary finding in these trials was that patients who took almotriptan early, when the pain was still mild, achieved better outcomes. This prompted the initiation of studies designed to assess the effect of almotriptan in early intervention. Open-label trials reported improvements in pain-free end points (2 h, 24 h), and subsequent RCTs confirmed these findings. Pharmacovigilance data from more than 100 million tablets dispensed worldwide have confirmed that almotriptan is associated with a low occurrence of adverse effects, which, in clinical trials, has been shown to be similar to that observed with placebo. The clinical evidence obtained and comparisons made over a decade of use have demonstrated that almotriptan is one of the more effective and fast-acting triptans available, with a placebo-like tolerability profile. This suggests that almotriptan is an excellent choice for patients requiring specific acute migraine treatment.